Perceptions of the People of South Sulawesi Regarding the 2024 Presidential General Election - Nurfadilah Nasiruddin; Dewi Nuraliah; Mausili, Dwi Rianisa; Muhamad Arsat (Kirana Publisher (KNPub), 2023)
The Presidential General Election will be held in 2024, several names of presidential candidates are starting to appear on social media and electronic media. With the emergence of these various candidates, it is important to know the public's perception of the 2024 general election. This research aims to analyze the public's perception of the 2024 general election. This research uses a qualitative descriptive research method with a survey method. Determining the sample in this study used non-probability sampling, namely Snowball sampling. All respondents came from South Sulawesi Province spread across several districts and were aged 19 years or over and had participated in previous general elections. The research results show that almost all respondents know that general elections will be held in 2024 and only half know that February 14 2024 is the schedule for the presidential general election. There are several factors that influence people's perceptions, namely background, experience, attention and mental readiness. These several factors produce several important things that are the focus or attention of the public regarding the 2024 general election. First, information about the profile of the presidential candidate, namely the vision, mission, goals and supporting parties of the presidential candidate. Second, information about the implementation of general elections, namely the general election system, conditions and procedures for holding elections, election supervision, voter list, election schedule, election budget and voting places/locations. And the final results show that almost all respondents have not yet decided on their presidential choice for the 2024 general election.